2020
DOI: 10.1016/j.jamcollsurg.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: Major Risk Factor for Morbidity and Mortality in Severely Injured Trauma Patients

Abstract: BACKGROUND: Metabolic syndrome (MetS) increases cardiovascular risk and is associated with poor patient outcomes. We hypothesized that MetS confers an increased risk of morbidity and mortality in severely injured trauma patients. STUDY DESIGN: We performed a retrospective review of trauma patients from 2014 through 2018, excluding patients younger than 16 years, with Injury Severity Score <16, and with incomplete height and/or weight documentation. Metabolic syndrome was defined as the presence of diabetes, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…There were 18 studies 89,127–143 (1,415,697 participants) with critically ill populations (Table S3): 11 cohorts in North America, 3 each were in East Asia and in Europe, and 1 in the Pacific. Mean age of participants ranged from 41 to 87 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 18 studies 89,127–143 (1,415,697 participants) with critically ill populations (Table S3): 11 cohorts in North America, 3 each were in East Asia and in Europe, and 1 in the Pacific. Mean age of participants ranged from 41 to 87 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were 18 studies 89,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143] (1,415,697 participants) with critically ill populations (Table S3): quadratic term for mean BMI with a linear term (Table 2) or when groups with mean BMIs <20 kg/m 2 were excluded. The interaction terms for Asian/non-Asian majority countries were non-significant.…”
Section: Critically Ill Populationsmentioning
confidence: 99%
“…Five interventional studies were related to Objective 1 (Atrous et al, 2021; Ghezeljeh et al, 2017; Powers, 2016; Rose et al, 2022; Sutton et al, 2013). Five case studies (Dambaugh & Ecklund, 2016; Spike, 2018; Tammellero, 2011; Tatusov et al, 2017; Temple et al, 2017), two qualitative studies (Barakat‐Johnson et al, 2019; Hales et al, 2018) and two mixed methods studies (Tanneberger & Ciupitu‐Plath, 2018; Walker et al, 2019) were related to Objective 2 and 28 quantitative studies— to Objective 3 (Amini et al, 2022; Buffon et al, 2022; Capasso et al, 2022; Carson et al, 2018; Coyer et al, 2014; Ditillo et al, 2014; Drake et al, 2010; Gardiner et al, 2014; Grap et al, 2019; Großschädl & Bauer, 2022; Hobson et al, 2017; Hyun et al, 2014; Kayser et al, 2019; Kottner et al, 2011; Litcherfeld‐Kottner et al, 2020; Mananzo et al, 2014; Miller et al, 2016; Ness et al, 2018; O'Brien et al, 2014; Pokorny et al, 2014; Qaddumi & Almahmoud, 2019; Raff et al, 2016; Swanson et al, 2011; Tracy et al, 2020; VanGilder et al, 2010, 2021; Verekova et al, 2020; Workum et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Three further studies found significant associations, including Grap et al (2019) in their multivariate model with BMI ≥ 30, low Braden (Braden & Bergstrom, 1987) score and OR time. Tracy et al (2020) found patients with metabolic syndrome and a BMI range of 32.1 to 37.3 had higher pressure injury occurrence than those without metabolic syndrome and a BMI of 22.6 to 29.8. Kayser et al (2019) found a U‐shaped relationship with low and high BMIs at the greatest risk for pressure injury, with a BMI of 40 to 45 providing reduced risk.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiovascular risk factors such as pre-injury warfarin usage, congestive heart failure, and pre-injury beta-blocker use, as well as combinations of these conditions, which result in the greatest mortality rates, increase the chance of trauma death [ 41 , 42 ]. The ‘metabolic syndrome’ (combination of unfavorable factors diabetes, hypertension and BMI >30 kg/m 2 ) is strongly associated with increasing length of hospital stay, occurrence of cardiac arrest and myocardial infarction and is an independent death -predictor, which should be identified early in order to facilitate prompt multidisciplinary treatment [ 43 ]. Our findings that polytrauma patients with cardiac comorbidities have significantly higher concentrations of troponin T, IL-33R, higher BMI and initial sugar level are in accordance with this, and further emphasize the need for a specialized, multidisciplinary therapeutic strategy for patients with polytrauma and cardiac comorbidities.…”
Section: Discussionmentioning
confidence: 99%